Peranan Teknologi Mesin Elektrolizer sebagai Penghasil Sodium Hyphochlorite pada Pembangkit PT.Indonesia Power UJP PLTU Banten 2 Labuan - Fitriani Fitriani; Siswo Wardoyo (Politeknik Kampar, 2025)
This research aims to discuss electrolyzer technology which acts as a tool that produces sodium hypochlorite or chlorine active ingredient. Sodium hypochlorite functions as an active ingredient that can weaken and neutralize microorganisms so that the cooling channel (condenser) is protected from the proliferation of marine life that can inhibit the channel. The research method carried out is explanatory descriptive research, while the method of data collection is carried out through observation and interviews with related parties. The process carried out to make sodium hypochlorite or chlorine products begins with seawater entering the sea water tank, sea water booster pump, sea water strainer, electrolyzer, sodium hyphochlorite tank, continuous dosing pump, shock dosing pump and finally injection intake area. The main tool used to produce sodium hypochlorite is an electrolyzer, this tool functions as a separator of seawater compounds to be used as sodium hypochlorite or chlorine active ingredient. The results showed that the electrolyzer technology produces active ingredients that can weaken marine biota to prevent blockages in the condenser channel. The existing cooling system works optimally so that the plant avoids overheating.